The Role of Clopidogrel in 2020: A Reappraisal - Giuseppe Patti; Giuseppe Micieli; Claudio Cimminiello; Leonardo Bolognese (Hindawi-Wiley, 2020)
Antiplatelet therapy is the mainstay of treatment and secondary prevention of cardiovascular disease (CVD), including acute coronary syndrome (ACS), transient ischemic attack (TIA) or minor stroke, and peripheral artery disease (PAD). The P2Y12 inhibitors, of which clopidogrel was the first, play an integral role in antiplatelet therapy and therefore in the treatment and secondary prevention of CVD. This review discusses the available evidence concerning antiplatelet therapy in patients with CVD, with a focus on the role of clopidogrel. In combination with aspirin, clopidogrel is often used as part of dual antiplatelet therapy (DAPT) for the secondary prevention of ACS. Although newer, more potent P2Y12 inhibitors (prasugrel and ticagrelor) show a greater reduction in ischemic risk compared with clopidogrel in randomized trials of ACS patients, these newer P2Y12 inhibitors are often associated with an increased risk of bleeding. Deescalation of DAPT by switching from prasugrel or ticagrelor to clopidogrel may be required in some patients with ACS. Furthermore, real-world studies of ACS patients have not confirmed the benefits of the newer P2Y12 inhibitors over clopidogrel. In patients with very high-risk TIA or stroke, short-term DAPT with clopidogrel plus aspirin for 21-28 days, followed by clopidogrel monotherapy for up to 90 days, is recommended. Clopidogrel monotherapy may also be used in patients with symptomatic PAD. In conclusion, there is strong evidence supporting the use of clopidogrel antiplatelet therapy in several clinical settings, which emphasizes the importance of this medication in clinical practice.